2020
DOI: 10.1002/jtr.2410
|View full text |Cite
|
Sign up to set email alerts
|

Yuanfen and traveling neo‐tribes: Social interactions and group relations among Chinese road travelers

Abstract: Within the context of Chinese culture and the theoretical framework of neo-tribes, this study explores the mobilities of road travelers on the Sichuan-Tibet Highway in China and explains their social interactions and group relations by using mobile ethnography and multi-sited ethnography. It finds that social interactions during road travels are "easily meet, easily part." However, between travelers and within travel groups, kindness and affective interactions are ubiquitous. The Chinese cultural concept "yuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Currently, only several recent studies (i.e. Jiang et al , 2022; Wang and Xie, 2021; Zhang et al , 2020) have discussed yuanfen in the accommodation or travel context. In the travel context, a sense of having yuanfen with other tourists is found to influence travel experiences (Wang and Xie, 2021), whereas yuan-connected strangers help foster tourists’ sense of place (Jiang et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only several recent studies (i.e. Jiang et al , 2022; Wang and Xie, 2021; Zhang et al , 2020) have discussed yuanfen in the accommodation or travel context. In the travel context, a sense of having yuanfen with other tourists is found to influence travel experiences (Wang and Xie, 2021), whereas yuan-connected strangers help foster tourists’ sense of place (Jiang et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the existing studies argued that perceived yuanfen influences customer experiences (Zhang et al , 2020). However, they also found that customers attribute positive experiences to yuanfen (Wang and Xie, 2021). Thus, the causal relationship between customer experiences and perceived yuanfen is still ambiguous.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Travel on a transport artery generates a plethora of social encounters between strangers, shaped by the duration, hardship and riskiness of the journey (Wang and Xie, 2021). Along the major routes leading to Tibet, those who travel by cars may show gestures of respect to the hikers and cyclists met on the road.…”
Section: More‐than‐representational Encountersmentioning
confidence: 99%
“…Since then, the neo tribal theory has been accepted as an alternative to subculture theory. The theory is first used in sociological researches (Bennett, 1999;Hetherington, 1998;Hughson, 1999), then in marketing researches (Cooper, McLoughlin, & Keating, 2005;Cova & Cova, 2001), and recently in recreation and tourism researches (Goulding & Shankar, 2011;Hardy & Robards, 2015;Hardy, Dolnicar, & Vorobjovas-Pinta, 2021;St John, 2018;Vorobjovas-Pinta, 2018;Vorobjovas-Pinta & Lewis, 2021;Wang & Xie, 2021;Weaver, 2011;Wu & Dai, 2019). Therefore, neo tribal theory can be considered as a guide to understanding the social behaviors of travelers or tourists.…”
Section: Neo Tribes and Drug Touristsmentioning
confidence: 99%
“…Results revealed the origin of the neo tribe, as a support mechanism for homeowners and a challenge to perceived marginalization by the tourism industry that refuses to embrace their hosts. Within the theoretical framework of neo tribes, Wang and Xie (2021) explored the mobilities of road travelers on the Sichuan-Tibet Highway in China and explained their social interactions. They found that social interactions during road travels are 'easily meet, easily part.'…”
Section: Neo Tribes and Drug Touristsmentioning
confidence: 99%